Analysis of Wear Properties of Powder Metallurgy Steel in Abrasive Soil Mass - Lemecha, Magdalena; Napiórkowski, Jerzy; Ligier, Krzysztof; Tarasiuk, Wojciech; Sztukowski, Krzysztof (Materials, 2022)
This study presents the results of testing for abrasive wear of Vanadis 60 SuperClean powder metallurgy steel as compared to Hardox 600 steel and PMFe60P padding weld. The testing was conducted by the “rotating bowl” method using natural abrasive soil masses. Two types of abrasive masses with particle size distributions corresponding to light soil and medium soil were used. The obtained results enable the conclusion that the weight loss for Vanadis 60 SuperClean powder steel in both types of abrasive mass was approximately seven times lower than that for Hardox 600 steel and two times lower than PMFe60P padding weld. The high resistance of powder steel to abrasive wear in abrasive soil masses is related to the presence of a large number of fine M6C (tungsten-molybdenum) and MC (vanadium) carbide precipitates in its microstructure. The obtained test results indicate that the application of Vanadis 60 SuperClean steel may be extended to working elements operating in mineral abrasive environments.